Pengembangan Game Digital Kontekstual “Petualangan Sistem Pencernaan” untuk Meningkatkan Kreativitas dan Hasil Belajar Siswa SMP - Gusti Nida Nurkhaliza; Mohamad Nor Aufa; Chandra Anugrah Putra; Muqor Rama Hasanah; Muhammad Hasbie; Najwa Azahra; William Hans Permana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop and examine the effectiveness of a contextual digital game entitled “Digestive System Adventure” in improving students’ creativity and learning outcomes at the junior high school level. The method used was Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The game product was developed as a web-based application using HTML, CSS, and JavaScript, organized into several levels featuring interactive activities such as drag-and-drop, sequencing, matching, and contextual classification, and equipped with a scoring system and feedback. The results showed that the developed media was categorized as highly feasible based on expert validation of media and content. Furthermore, the contextual digital game proved to be more effective in improving students’ learning outcomes and creativity compared to conventional learning methods. In conclusion, the contextual digital game “Digestive System Adventure” is feasible and effective for enhancing students’ creativity and learning outcomes. Keywords: Creativity, Digital Game Media, Learning Outcomes, Digestive System, Contextual